2021
DOI: 10.1186/s13098-021-00669-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of citrulline supplementation on meta-inflammation and insulin sensitivity in type 2 diabetes: a randomized, double-blind, placebo-controlled trial

Abstract: Background This study aimed to examine the effects of l-citrulline (l-CIT) on low-grade inflammation (meta-inflammation) and insulin sensitivity in type 2 diabetes (T2D) patients since it has exhibited hypoglycemic and anti-inflammatory effects in most animal studies. Methods In this double-blind, placebo-controlled randomized clinical trial, 54 patients with T2D referred to specialized clinics of Tabriz University of Medical Sciences were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…In contrast, citrulline, which was signi cantly reduced in serum of MUO compared to MHO in the present study, appears to play a role in arterial dilation and glucose homeostasis 42 . A randomized double-blind-placebo controlled study revealed that citrulline supplementation was able to markedly reduce value of fasting blood glucose and HbA1c in humans 43 . Lastly, concentration of betaine in serum, a naturally occurring methyl donor, which was signi cantly decreased in the MUO compared to MHO, is known to associate with metabolically-bene cial pro le in Asian men with mild fatty liver disease 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, citrulline, which was signi cantly reduced in serum of MUO compared to MHO in the present study, appears to play a role in arterial dilation and glucose homeostasis 42 . A randomized double-blind-placebo controlled study revealed that citrulline supplementation was able to markedly reduce value of fasting blood glucose and HbA1c in humans 43 . Lastly, concentration of betaine in serum, a naturally occurring methyl donor, which was signi cantly decreased in the MUO compared to MHO, is known to associate with metabolically-bene cial pro le in Asian men with mild fatty liver disease 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, citrulline, which was significantly reduced in serum of MUO compared to MHO in the present study, appears to play a role in arterial dilation and glucose homeostasis 39 . A randomized double-blind-placebo controlled study revealed that citrulline supplementation was able to markedly reduce value of fasting blood glucose and HbA1c in humans 40 . Lastly, concentration of betaine in serum, a naturally occurring methyl donor, which was significantly decreased in the MUO compared to MHO, is known to associate with metabolically-beneficial profile in Asian men with mild fatty liver disease 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the disturbances of the L-arginine-NO-L-citrulline pathway in diabetes and metabolic syndrome are closely related to inflammation and oxidative stress [ 64 ]—the hallmarks of diabetic vascular complications [ 36 ]. At the same time, it was demonstrated that L-citrulline supplementation increases NO levels [ 65 ], improves insulin resistance, and decreases HbA1c and concentrations of inflammatory markers in patients with T2D [ 66 , 67 ]. The abnormalities of L-citrulline metabolism in diabetes, along with the mechanisms of their relationship with vascular disease, merit further research.…”
Section: Discussionmentioning
confidence: 99%